You Want to Do What with Doda’s Stories? Building a Community for the Skins Workshops on Aboriginal Storytelling in Digital Media - Lewis, Jason E.; Fragnito, Skawennati (Community-Based Multiliteracies & Digital Media Projects : Questioning Assumptions and Exploring Realities, 2014)
Aboriginal Territories in Cyberspace (AbTeC) is a research network of artists, academics and technologists centrally concerned with Indigenous representation in, and production of, digital media (AbTeC, 2008). AbTeC investigates and identifies ways for Indigenous peoples to tell our stories via networked technologies, and in so doing, strengthen our communities while proactively participating in shaping cyberspace. We are based at Concordia University, in Montreal, Quebec.
Keywords: 1-Histoire de l'art; 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé